Composición de miniaturas para piano a partir de los CUATRO RAYMIS característicos de la cultura Saraguro. - Poma Guaman, Fredy Oswaldo (2022)
Several works study the Ecuadorian culture's development, its customs, and traditions. This research is focused on the Saraguro culture, which has a number of festivities and traditional celebrations, such as the Raymis: Kulla Raymi, Kapak Raymi, Pawkar Raymi, Inti Raymi. However, a large part of the people from the Oñacapac community, who are part of the indigenous town of Saraguro, do not know the meaning of such customs and traditions nor the connotation of these celebrations in the Andean worldview. In order to contribute to fill this gap, the general goal was to compose four piano miniatures, taking the Raymis celebrations with their particularities in Saraguro culture as reference. To contrast the origin and features of each celebration, the bibliographic study was completed with the oral testimony of four important people related to these events. With the results of this study, the obtained information about the celebrations of the Raymis was used to develop the compositional proposal: musical genres involved in each celebration were identified, and four miniatures for the piano were created, one for each Raymi. These musical pieces contribute to the appreciation of Saraguro people’s music and, at the same time, provide an input of reference for future research. Finally, this research work and its artistic product contribute to the research project named: “Creation, production and diffusion of musical works in the National University of Loja, during 2022-2023”. We recommend the Lojan and Ecuadorian musical community to know more about musical aspects of autochthonous culture in order to take benefit from its richness. Key words: Saraguro, intercultural music, Raymi, and piano